2018
DOI: 10.1039/c8ra03480j
|View full text |Cite
|
Sign up to set email alerts
|

Recent metal-catalysed approaches for the synthesis of cyclopenta[b]indoles

Abstract: This review provides a summary of recent metal-catalysed approaches for the synthesis of cyclopenta[b]indoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 83 publications
0
38
0
2
Order By: Relevance
“…(Table 1, entries 1-10) Further optimization with a set of representative solvent, CH 3 CN, 1,4-dioxane, MeOH, toluene, DMF and DMSO gave unsatisfied results. (entries 12-17) Screening of the additives indicated that Cu(OTf) 2 and AgOTf exhibited similar efficiency, affording product 3 aa in 85% and 82% yield respectively, (entries 18 and 22) whereas other additives, including AgTFA, Zn(OTf) 2 and CF 3 CO 2 H only gave inferior results (entries [19][20][21]. Decreasing or increasing the reaction temperature led to a lower yield (entries 23 and 24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Table 1, entries 1-10) Further optimization with a set of representative solvent, CH 3 CN, 1,4-dioxane, MeOH, toluene, DMF and DMSO gave unsatisfied results. (entries 12-17) Screening of the additives indicated that Cu(OTf) 2 and AgOTf exhibited similar efficiency, affording product 3 aa in 85% and 82% yield respectively, (entries 18 and 22) whereas other additives, including AgTFA, Zn(OTf) 2 and CF 3 CO 2 H only gave inferior results (entries [19][20][21]. Decreasing or increasing the reaction temperature led to a lower yield (entries 23 and 24).…”
Section: Resultsmentioning
confidence: 99%
“…[1] Thus, the modifications of indoles and indolines for the diversification of the scaffolds have received increasing attentions over the last few years. [2] Recent advances in the transitionmetal catalysed direct CÀ H functionalization provided a powerful strategy for the modification of indole and indoline structures. [3] Nevertheless, the derivation of indoles and indolines were generally limited to the C 1 -C 4 and C 7 positions governed by the effect of directing groups or the inherent nucleophilic reactivity, [4] while the site-selective CÀ H functionalization on the remote less activated C 5 position has remained a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…We hereby report a new advance which is a visible‐light‐induced, Gd III ‐catalyzed, regioselective, intermolecular [2+2] cycloaddition/ring‐expansion sequence with indoles, providing facile and divergent access to cyclopenta[ b ]indoles and indolines (Figure b). These obtained compounds are privileged scaffolds among numerous natural products and drug candidates (Figure c) . Differing from the previous report on using elaborately synthesized Gd III ‐porpholactone complexes in photocatalysis, the simple and commercially available salt Gd(OTf) 3 is sufficient for this transformation.…”
Section: Introductionmentioning
confidence: 97%
“…These obtained compounds are privileged scaffolds among numerous natural products and drug candidates ( Figure 2c). [18] Differing from the previous report on using elaborately synthesized Gd III -porpholactone complexes in photocatalysis, [7] the simple and commercially available salt Gd(OTf) 3 is sufficient for this transformation. Furthermore,t his unprecedented method features readily available feedstocks,m ild conditions,p rotecting group free, high regioselectivity,b road scope and multi-step transformations in one pot.…”
Section: Introductionmentioning
confidence: 99%